Clinical epidemiology of long-term suicide risk in a nationwide population-based cohort study in South Korea. (May 2018) - Lee, Hyewon; Myung, Woojae; Lee, Chunsoo; Choi, Junbae; Kim, Ho; Carroll, Bernard J.; Kim, Doh Kwan
Abstract: We investigated the effects of a large range of clinical factors on the long-term risk of suicide in the general population of South Korea. We analyzed the National Health Insurance Service-National Sample Cohort (NHIS-NSC) database in South Korea. A total of 300, 232 individuals were followed for up to 12 years. We obtained information on demographic variables (age and sex), lifestyle variables (cigarette smoking, alcohol drinking and exercise), psychiatric and physical disorders, laboratory examination results and physical examination findings. We conducted a competing risk survival analysis to estimate the risk of completed suicide. 725 individuals (241/100, 000) died by suicide in the follow-up period. After Bonferroni correction, we found a significant suicide risk associated with 6 variables: Parkinson's disease, depressive disorder, obsessive-compulsive disorder (inverted association), elevated serum aspartate aminotransferase levels, male gender and age. Before Bonferroni correction, variables such as cigarette smoking, heavy alcohol drinking, psychotic disorder, other psychiatric disorder, benzodiazepine use and higher fasting glucose showed some significant association. In addition, body mass index and height were inversely related to completed suicide before Bonferroni correction. However, only the 6 variables listed above were robust predictors of suicide in the fully adjusted analyses with multiple test correction. Common medical conditions had no clear influence on suicide. Diverse clinical factors influenced the long-term risk of completed suicide in this general population sample. Comprehensive assessment of these risk factors will facilitate more focused suicide surveillance measures.